INSULIN RESISTANCE AS A RISK FACTOR FOR COGNITIVE DYSFUNCTION - Antoniya Hachmeriyan; Nadezhda Stefanova; Gabriela Panayotova (Journal of IMAB)
Introduction: Epidemiologic, experimental, and clinical data support a link between type 2 diabetes mellitus (T2DM) and dementia due to Alzheimer's disease (AD). The prevalence of both T2DM and AD increases with age, and both diseases are chronic and are among the leading causes of morbidity and mortality. AD incidence in late diabetic patients is two times higher compared with normal elderly people and is thought to arise from impaired insulin secretion and resistance, leading to nervous system damage and ultimately influencing cognitive function in patients. Material and methods: Using representative keywords, we conducted a comprehensive search in the scientific web databases PubMed and Scopus and limited the publication date of the papers to the last 10 years. Results: Insulin resistance (IR) causes long-term neuronal exposure to a high-level insulin environment, leading to neuronal degeneration and irreversible memory impairment. The review of the literature outlined several possible mechanisms for IR and cognitive dysfunction interplay: (1) IR affects hippocampal plasticity, (2) IR contributes to altered amyloid precursor protein (APP) metabolism, (3) IR is related to elevated tau protein concentration, (4) IR affects brain inflammatory reaction, (5) oxidative stress is identified as an early event in the development of brain IR, and (6) genetic factors, related to ApoE ε4 allele expression and IR are present. Conclusion: Although secreted peripherally, insulin plays a profound role in cognitive function, and IR facilitates the brain's susceptibility to neurodegeneration. The brain insulin signaling pathways also offer a promising therapeutic target for managing cognitive disorders.